2023
DOI: 10.3389/fpls.2023.1218734
|View full text |Cite
|
Sign up to set email alerts
|

Chilling temperatures and controlled atmospheres alter key volatile compounds implicated in basil aroma and flavor

Abstract: Use of basil in its fresh form is increasingly popular due to its unique aromatic and sensory properties. However, fresh basil has a short shelf life and high chilling sensitivity resulting in leaf browning and loss of characteristic aroma. Moderate CO2 atmospheres have shown potential in alleviating symptoms of chilling injury in basil during short-term storage but its effect on the flavor volatiles is unclear. Moreover, studies on basil volatile profile as impacted by chilling temperatures are limited. We in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
(99 reference statements)
0
3
0
Order By: Relevance
“…Although 0% CO 2 is ideal for basil storage in N 2 , slightly raising CO 2 levels may benefit storage under ambient air. Storage in 5% CO 2 at 5°C minimized the symptoms of chilling injury for up to 3 days in Genovese sweet basil, though not in lemon basil when compared to 0.04% CO 2 (Rodeo and Mitcham, 2023). Although the conclusions of this study cannot be certain as they did not standardize O 2 levels, the results are consistent with a prior study that found adding 2.5 kPa CO 2 to air effectively inhibited leaf abscission, decay and browning in storage at 12°C for 7 days, especially when combined with a single pre-treatment of 0.7 mmol•L -1 1-methylcyclopropene (1-MCP), which is a synthetic growth regulator used to maintain freshness (Kenigsbuch et al, 2015).…”
Section: Controlled Atmospherementioning
confidence: 91%
See 2 more Smart Citations
“…Although 0% CO 2 is ideal for basil storage in N 2 , slightly raising CO 2 levels may benefit storage under ambient air. Storage in 5% CO 2 at 5°C minimized the symptoms of chilling injury for up to 3 days in Genovese sweet basil, though not in lemon basil when compared to 0.04% CO 2 (Rodeo and Mitcham, 2023). Although the conclusions of this study cannot be certain as they did not standardize O 2 levels, the results are consistent with a prior study that found adding 2.5 kPa CO 2 to air effectively inhibited leaf abscission, decay and browning in storage at 12°C for 7 days, especially when combined with a single pre-treatment of 0.7 mmol•L -1 1-methylcyclopropene (1-MCP), which is a synthetic growth regulator used to maintain freshness (Kenigsbuch et al, 2015).…”
Section: Controlled Atmospherementioning
confidence: 91%
“…Sudden declines in basil volatile compounds have been observed even earlier after only 3 days at 5°C (Rodeo and Mitcham, 2023). While some secondary metabolites such as carotenoids and a Minimize chilling injury (Lange and Cameron, 1994;Lange and Cameron, 1997;Meir et al, 1997;Rodeo and Mitcham, 2023), microbial growth (da Silva et al, 2005;Delbeke et al, 2015) and loss of volatile aroma compounds, polyphenols and antioxidants (Sharma et al, 2005;Loṕez-Blancas et al, 2014;Cozzolino et al, 2016;Ghasemzadeh et al, 2016;Fratianni et al, 2017;Rodeo and Mitcham, 2023) Artificial handful of volatile compounds were better conserved at 4-5°C compared to 12-20°C, relatively higher storage temperatures are favorable for the major volatiles responsible for aroma in basil (Loṕez-Blancas et al, 2014;Cozzolino et al, 2016;Rodeo and Mitcham, 2023). Contrary to preserving leaf freshness and aroma, storing basil at cooler temperatures of <15°C is favorable for inhibiting fungi and bacteria (da Silva et al, 2005;Delbeke et al, 2015).…”
Section: Storage Temperaturementioning
confidence: 99%
See 1 more Smart Citation